Productivity of Maize Genotypes under Different Planting Dates (Our Nature, 2015)
Genotypic yield potential of maize genotypes is greatly affected by planting dates. This study was conducted to determine optimum planting dates of maize genotypes in 2013/14 at Rampur, Chitwan, Nepal. Four genotypes namely RML-4/RML-17, RML-32/RML-17, ACROSS-9944/ACROSS-9942 and S99TLYQ-B were planted at every week from April  to March.  The experiments were laid out in randomized complete block design with four replications . The result of experiment showed that the highest production (5565 kg/ha) was obtained in August followed by February (5266 kg/ha), June (4475 kg/ha) and July (4255 kg/ha) respectively. The lowest yield (2572 kg/ha) was obtained in the month of November and December planting (3019 kg/ha). The highest grain yield was obtained in RML-4/RML-17 (7392 kg/ha) and RML-32/RML17 (6606 kg/ha), ACROSS- 9944/ACROSS-9942 (5004 kg/ha) during August planting and higher yield of QPM variety S99TLYQ-B was obtained in the month February planting. Winter maize has higher production potential than the rainy season maize. Based on this experiment RML-4/RML-17, RML-32/RML17 and ACROSS- 9944/ACROSS-9942 should be planting in August (winter season) and S99TLYQ-B in February (spring season) for higher grain yield production.Our Nature (2015), 13(1): 45-49